2019
DOI: 10.21837/pmjournal.v17.i10.654
|View full text |Cite
|
Sign up to set email alerts
|

Respondents’ Area of Preference When Disaster Strikes: A Case Study of Cameron Highland

Abstract: Disaster can be understood as the probability or threat of quantifiable damage, injury, liability, loss, or any other negative occurrence that is caused by external or internal vulnerabilities that required an immediate action. Therefore, this study intends to understand respondents’ preferences of location when disaster strikes their settlements/ villages. Their responses are important to indicate their preparedness when facing disaster. Data collection was employed using the questionnaire survey method to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Meanwhile, certain tourism and land use activities play a role in increasing the environmental risk (Lequy et al 2019;Rabe et al, 2019& Latip et al, 2020 such the level of heavy metal concentration within plant. In the light of heavy metals concentrations in mosses, the result confirmed that a higher value of aluminium heavy metal concentrations was found in Abu Suradi trail within Fraser's Hill and Brinchang Trail.…”
Section: Conclusion Relation Of Moss Species With Local Microclimate and Heavy Metal Concentrationmentioning
confidence: 99%
“…Meanwhile, certain tourism and land use activities play a role in increasing the environmental risk (Lequy et al 2019;Rabe et al, 2019& Latip et al, 2020 such the level of heavy metal concentration within plant. In the light of heavy metals concentrations in mosses, the result confirmed that a higher value of aluminium heavy metal concentrations was found in Abu Suradi trail within Fraser's Hill and Brinchang Trail.…”
Section: Conclusion Relation Of Moss Species With Local Microclimate and Heavy Metal Concentrationmentioning
confidence: 99%